Evaluation of English Language Material for the 9th Grader Student at SMP Nurul Islam Ngemplak Boyolali - Wiratmoko, Gandung; Muamaroh, Muamaroh; Adityarini, Hepy (Journal of Education Method and Learning Strategy, 2024)
Teaching language in this global era demands mostly the creativity of the teachers, this is because in 21th century, students need to be critical thinkers, creative, communicative and collaborative. Therefore, the creativity of the teacher is manifested by evaluating the multiple resources and adapting or adopting them based on the contextualized learning situation including individual differences, styles and learners needs. It is also essential for the teacher to integrate the four macro skills in teaching language in order to make the students more communicative and collaborative. Hence, this paper presents the evaluation of the language teaching resources before and during applying them to the classroom contexts. The data were collected by document review and interview with the secondary school teacher. The data were analyzed qualitatively through interactive model. There is variation of the results based on the techniques of data collection. The interview shows that theoretically the teacher is creative to make the materials for students. Meanwhile, the document review findings show that there is a need of improvement on the way to evaluate and use the English materials based on the context. Finally, in evaluating the textbooks in order to adopt or adapt by adding or removing some materials to make English textbooks match with students’ contexts. Keywords evaluation, adapting, adopting, macro skills, English language teaching.